Longer Preoperative Duration of Symptoms Negatively Affects Health-related Quality of Life After Surgery for Cervical Radiculopathy. Issue 10 (15th May 2019) - Tarazona, Daniel; Boody, Barrett; Hilibrand, Alan S.; Stull, Justin; Bell, Kerri; Fang, Taolin; Goyal, Dhruv; Galetta, Matthew; Kaye, David; Kepler, Christopher K.; Kurd, Mark F.; Woods, Barrett I.; et al.
Abstract : Study Design: Retrospective cohort. Objective: Determine the effect of duration of symptoms (DOS) on health-related quality of life (HRQOL) outcomes for patients with cervical radiculopathy. Summary of Background Data: The effect of DOS has not been extensively evaluated for cervical radiculopathy. Methods: A retrospective analysis of patients who underwent an anterior cervical decompression and fusion for radiculopathy was performed. Patients were grouped based on DOS of less than 6 months, 6 months to 2 years, and more than 2 years and HRQOL outcomes were evaluated. Results: A total of 216 patients were included with a mean follow-up of 16.0 months. There were 86, 61, and 69 patients with symptoms for less than 6 months, 6 months to 2 years, and more than 2 years, respectively. No difference in the absolute postoperative score of the patient reported outcomes was identified between the cohorts. However, in the multivariate analysis, radiculopathy for more than 2 years predicted lower postoperative Short Form-12 Physical Component Score ( P = 0.037) and Short Form-12 Mental Component Score ( P = 0.029), and higher postoperative Neck Disability Index ( P = 0.003), neck pain ( P = 0.001), and arm pain ( P = 0.004) than radiculopathy for less than 6 months. Furthermore, the recovery ratios for patients with symptoms for less than 6 months demonstrated a greater improvement in NDI, neck pain, and arm pain than for 6 months to 2 years ( P = 0.041; 0.005; 0.044) and more than 2 years ( P = 0.016; 0.014; 0.002), respectively. Conclusion: Patients benefit from spine surgery for cervical radiculopathy at all time points, and the absolute postoperative score for the patient reported outcomes did not vary based on the duration of symptoms; however, the regression analysis clearly identified symptoms for more than 2 years as a predictor of worse outcomes, and the recovery ratio was statistically significantly improved in patients who underwent surgery within 6 months of the onset of symptoms. Level of Evidence: 3 Abstract : The impact of duration of cervical radiculopathy symptoms on surgical outcomes is poorly understood. A retrospective study demonstrated that longer than 6 months of symptoms resulted in less improvement in disability and pain than less than 6 months of symptoms. Furthermore, symptoms longer than 2 years predicted worse postoperative outcomes.